Um ambiente de monitoramento para sistemas multi-robôs com cossimulação federada e Hardware-in-the-Loop - Costa, Luís Feliphe Silva (2016)
Simulations often are used in development systems do predict how systems will work on final environment. Many kinds of simulations and techniques are available, one of then is Hardware-in-the-Loop Simulation that provides a more realistic environment by using real devices on simulations. In this work this technique is used with co-simulation between Ptolemy and Stage to provide an multi-robot environment and embedded systems design. It can help to find hardware and software errors during development. High Level Architecture, an IEEE pattern to interoperability between simulators is used to manage time and data that is shared on co-simulation. This work also studies synchronization aspects and uses real robots on simulations to validate proposed environment.